PERBANDINGAN HUKUM GADAI SYARIAH DENGAN GADAI KONVENSIONAL PADA PT. PEGADAIAN PEKANBARU - SITI SUHAINA; Mardalena Hanifah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Pawn is an insurance agency that has been very well known and in public life, in an attempt to obtain funds to share the needs of legal transactions pawn in Islamic jurisprudence called ar-Rahn. Arrahn is an agreement to hold an item as a dependent on debt and the lien conventional and syariah pawn has similarities and differences in the application of the concept of the pawn.In this study, the problem is how differences in syariah pawn agreement with the conventional mortgage and how equality in Islamic pawn contract conventional mortgage. Based on the research results, the equation contract pawn Islamic and pawn conventional mortgage, namely: the pawn is a guarantee that a person can pay its debts and if it fails to fulfill the rights of creditors to take payment of the object guarantees, the subject of the pledge is the recipient pledge and the pledgor, goods pawned both in terms of pawn islamic and conventional mortgage is not taken advantage, the recipient pawn has the right to sell the goods as collateral if the debt is not able to repay their debts, and shall keep and maintain the goods as collateral, and the pledgor is entitled to receive the remainder of the results of execution and required to settle the obligation. While differences in syariah and conventional mortgage lien, namely in terms of the legal basis where sharia lien based on the Qur'an, Hadith, consensus, and the MUI Fatwa, while pawn konvensioal by the Civil Code, conventional mortgage agreement only 1 (one) while at Rahn ( sharia), 2 (two) contract, fixing a day on conventional mortgage is determined per 15 days while at rahn (sharia) is determined per 10 day period in the conventional mortgage up to 3 months while on rahn (sharia) based on the calculation that there is, in the case taking the money from the auction of the lien, if within one year not taken the rest of the money is executed then becomes property of the pawnshop while in rahn if the remaining money from the auction results are not taken then it will be submitted to the Agency Amil Zakat (BAZ), the estimated goods in pawn sharia greater than estimated in the conventional mortgage, the decision marhun on syariah pawn directly come on the appointed day, while on a conventional mortgage should contact the cashier one day prior to the decision.Keywords: Comparison of Islamic Pawn - Pawn Conventional - PT. pawnshop Pekanbaru